Analysis of Coastal Line Changes in Coastal Area of the Pantai Cermin and Perbaungan Sub District, Serdang Bedagai District - Ramadhan, Alif Ridho; Mubarak, Mubarak; Mulyadi, Aras (Journal of Coastal and Ocean Sciences, 2022)
This research was conducted in January 2021 in the Coastal Area of ​​ Pantai Cermin and Perbaungan Districts, Serdang Bedagai Regency. The purpose of this study is to analyze shoreline changes from 1985 to 2021 and predict shoreline changes for 2040 in the Coastal Area of ​​ Pantai Cermin and Perbaungan Districts, Serdang Bedagai Regency. The method used is the survey method. The analysis was carried out using the Digital Shoreline Analysis System (DSAS) The results showed that the Coastal Area of Pantai Cermin and Perbaungan District, Serdang Bedagai Regency had experienced 89.62% abrasion and 10.38% accretion. With this, it can be seen that the Coastal Areas of Pantai Cermin and Perbaungan Subdistricts have mostly experienced an abrasion. Oceanographic factors in the waters of the Malacca Strait, such as currents and waves, the existence of poor mangrove forests, sloping water topography, and human activities in every part of the research area. Prediction results of shoreline changes in 2040 the abrasion are 319.1 m, while the accretion is 239.7 m.